(untitled) (Global Journal of Medical Research, 2020)
Asthma is a heterogeneous chronic airway disease with several distinct phenotypes characterized by different immune pathological pathways, clinical features, disease severity, physiology, and response to treatment. Approximately 50% of patients with stable chronic asthma have the eosinophilic phenotype, whereas the remainder have the non-eosinophilic asthma. Eosinophilic asthma is the most common phenotype in children with acute severe asthma, but neutrophilic asthma is the most common in adult patients presenting with acute severe asthma. T helper 2 (Th2) cytokines, such as interleukin-5 (IL-5), IL-4, IL-13, IL-25, IL-33, and thymic stromal lymphopoitein (TSLP), play a very important role in the pathophysiology of eosinophilic asthma. Interlukin-5 is the pivotal cytokine responsible for the proliferation, differentiation, activation, and survival of eosinophils; and promotion of eosinophil migration and airway eosinophilia. Activated eosinophils secrete granular cytotoxic cationic proteins, such as major basic protein, eosinophil cationic protein, eosinophil-derived neurotoxin, eosinohil-derived peroxide, and reactive oxygen species.